Software‐defined networking to improve handover in mobile edge networks. (29th June 2020) - Ahmadi, Kaveh; Miralavy, S. Pourya; Ghassemian, Mona
Summary: Mobility management and handover for a seamless connection are among all‐time challenges of wireless networks. Software‐defined networking (SDN) has opened new horizons toward research by adding intelligence in edge networks while decoupling the control and data planes. The flexibility and centralized nature of SDN further improve the handover decision algorithms. In this paper, we have improved the network performance with respect to the number of handovers and the handover delay by applying an LTE‐SDN architecture and a novel handover decision algorithm based on predicting the future locations of a moving vehicle. The proposed algorithm decouples the handover procedure into two phases of preparation and execution. In the preparation phase, which occurs in the control plane, the handover decision and resource allocation take place, and in the execution phase, handover gets executed similar to the LTE architecture. The results of our research indicate that our proposed LTE‐SDN performance is improved with respect to the number of handovers, handover delay, and signaling overhead by 24%, 16%, and 20%, respectively. On the other hand, average Reference Signal Received Quality (RSRQ) value is decreased by 4% as a tradeoff for the improvements gained. Abstract : In our work, we have proposed a novel handover decision algorithm based on an LTE‐SDN mobile edge networks architecture. We evaluate the traditional LTE architecture with A2A4 RSRQ handover decision algorithm by means of simulation. Furthermore, we have compared our proposed LTE‐SDN architecture with/without prediction with the traditional LTE architecture, and our results show improvements in terms of handover delay, number of handovers, and signaling overhead.